Effects of high-intensity interval training associated to microcurrent on localized adiposity: protocol of randomized clinical trial - Korelo, Raciele; Pesaski, Aline; Santos, Nandara Lopes dos; Silva, Natalia Paiva da; Anjos, Rubia Alana Souza dos; Vojciechowski, Audrin Said; Macedo, Ana Carolina Brandt de; Gallo, Rubneide Barreto Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: High-intensity interval training promotes body weight loss, while microcurrent electrical stimulation has therapeutic potential to reduce localized abdominal fat. However, there are no studies that have investigated the association of the two forms of intervention in reducing localized adiposity. Objectives: To verify the effects of high-intensity interval training, associated or not, with microcurrent therapy, in reducing localized abdominal fat. Methods: A randomized controlled clinical study will be conducted with 60 women aged 18 to 40 years, with localized abdominal adiposity. Participants will be randomized into 3 groups: Control Group (without physiotherapeutic intervention), Exercise Group (high-intensity interval training for 30 minutes) and Exercise Group associated with Microcurrent (application of 30 minutes of microcurrent prior to high-intensity interval training). The intervention will take place twice a week for 5 weeks. The clinical outcomes evaluated and their respective measuring instruments will be: body composition (bioimpedance scale and adipometry), anthropometric measurements (perimetry), level of physical activity (International Physical Activity Questionnaire - IPAQ, short version), quality of life (IWQol-Lite, short version), body satisfaction (Stunkard figure rating scale), degree of satisfaction with the performance of the intervention (questionnaire adapted by the researchers) and evaluation of the lumbopelvic complex. These outcomes will be measured in 4 moments: before the intervention, after the 5th and 10th intervention, and with a follow-up of 1 month. Discussion: A previous study has already shown the positive result of the association of moderate intensity exercise, associated with the previous application of microcurrent, in reducing localized abdominal adiposity. These findings raised the hypothesis that the association of this electrical therapy with high-intensity interval training may present positive results in the search for the reduction of abdominal fat, with the clinical advantage of enhancing the achieved results and/or reducing the time spent by the patient in therapy.